Kajian Jangkauan Layanan Stasiun KRL Jabodetabek di Wilayah Suburban (Studi kasus: Stasiun Tenjo dan Stasiun Tigaraksa) - Tinambunan, Hanna Dwipaningtyas Boru; Syabri, Ibnu (Jurnal Komposit: Jurnal Ilmu-ilmu Teknik Sipil, 2024)
The Jabodetabek commuter rail is an essential supporting public transportation system connecting suburban areas to city-centre workplaces. Determining service coverage is one thing that needs to be considered in a transit service availability system. This research tries to increase the range of services with park-and-ride and ridesourcing facilities at Jabodetabek commuter rail station locations in suburban areas. This is expected to increase interest in using the Jabodetabek commuter rail. For this reason, quantitative performance is needed to state what factors influence the service area coverage of a station in suburban areas, which are analyzed using the multiple linear regression method. Station service coverage is measured by the length of the journey from the place of residence to the starting station for Jabodetabek commuter rail users, with the station of origin of the trip being Tenjo Station and Tigaraksa Station, using the perspective of distance and travel time from the place of residence to the station of origin of the trip. The estimation results show that the radius of station service coverage, namely the travel time from residence to the station of origin of the journey (minutes), has a higher coefficient of determination than the distance from residence to the station of origin of the journey (km). Apart from that, 9 (nine) factors were identified that influenced travel time from residence to the station of origin of the journey (minutes). In contrast, the distance from residence to the journey's origin (km) station was identified as 6 (six) factors. Then, the estimated tolerance value for the station's service range is obtained in the range of 0.5-9.0 km and 5-26 minutes.